David Samuel Margoliouth on prophet’s monotheism: evaluation of his imagination - Muhammad, Akilu Aliyu; Abdul Rahim, Adibah (Department of Islamic History And Civilization, Academy of Islamic Studies, University of Malaya, 2018)
Prophet Muhammad’s monotheistic nature has been among the most debated issues in Muslim-Christian relation. Muslims in general believe that he was monotheist before, during and after he was sent as a Prophet. To support this claim, they provide some historical accounts which were found in his annals describing him as monotheist. On their side, the critics, more specifically, the christian appologists hold the opinion that he was not monotheist before his mission. Some of them have added that he was not monotheist even during and after his mission. they asserted that he adopted and continued to perform some rituals which were nothing more than idolatry during his mission and died an idolater without any hope of salvation. In their efforts to substantiate this claim, they cite some historical accounts which, they argue, depict him as idolater. This research therefore, attempts to analyse and evaluate the views of a Christian scholar, David Samuel Margoliouth, on this issue. Studies on his views regarding it seem to be more descriptive than analytical and evaluative. That probably happened because the researchers have not singled him out as a case study. Thus, their studies, although are vital, imperative and relevant appear to be laconic and sketchy as a result of which they have left lots of loopholes. This research, therefore, aims to carry out a wider analysis and evaluation of his views on this issue. However, this is a library based study. It is, therefore, a qualitative research. Thus, the principal approaches namely historical, analytical, evaluative and comparative have been widely used. Historical approach has been used in deliberation on the Prophet’s monotheistic nature before and during his mission. Textual as well as analytical approaches have been adopted in exploring his views on the Prophet’s montheism. Evaluative and comparative approaches have been adopted in assessing his views from the Islamic and realistic viewpoints.